2021
DOI: 10.1111/acer.14554
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Biomarkers in Patients With Alcohol Use Disorder and Persistent Cognitive Impairment

Abstract: Background The prevalence of cognitive impairment is high among alcohol‐dependent patients. Although the clinical presentation of alcohol‐related cognitive disorder (ARCD) may resemble that of Alzheimer’s disease (AD), the prognosis and treatment of the 2 diseases are different. Cerebrospinal fluid (CSF) biomarkers (tau, phosphorylated tau, and amyloid β) have high diagnostic accuracy in AD and are currently being used to discriminate between psychiatric disorders and AD, but are not used to diagnose ARCD. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In 15 severe ARCI patients, it was not observed a cognitive worsening of memory function at 6.5 months of follow-up, contrarily to AD patients. Moreover, in the very stringent severe ARCI group constituted to reduce clinical heterogeneity by having eliminated the others etiologies for dementia (Azuar et al, 2021) and where alcohol abstinence was documented and where continuous neuropsychological rehabilitation was delivered during a 9 month follow-up on average, it was observed a modest but statistically significant improvement on executive functions, discernible on the TMT-B test. The disease progression was different between severe ARCI and AD patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 15 severe ARCI patients, it was not observed a cognitive worsening of memory function at 6.5 months of follow-up, contrarily to AD patients. Moreover, in the very stringent severe ARCI group constituted to reduce clinical heterogeneity by having eliminated the others etiologies for dementia (Azuar et al, 2021) and where alcohol abstinence was documented and where continuous neuropsychological rehabilitation was delivered during a 9 month follow-up on average, it was observed a modest but statistically significant improvement on executive functions, discernible on the TMT-B test. The disease progression was different between severe ARCI and AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Malnourishment itself was defined as either weight loss ≥ 10%, with respect to any previously recorded weight from a previous medical record; or weight loss ≥ 5% in 1 month, with respect to a previously recorded weight; or Body Mass Index ≤ 17 kg/ m 2 , or serum albumin < 30 g/l; or serum prealbumin < 110 mg/l. Third, any other documented etiology for dementia (degenerative or vascular) had to be ruled out with the adequate brain imaging and/or cerebrospinal fluid examination (Azuar et al, 2021).…”
Section: Severe Alcohol-related Cognitive Impairments Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…The neuroprogression theory applies to AW leading to persistent cognitive deficits. But at the end of the evolution when a severe cognitive disorder is diagnosed in a patient with a past history of severe AUD, despite comprehensive etiological inquiry [ 82 ], it is impossible to differentiate the proper impact of repetitive AW from the neurotoxic effect of alcohol use. The effects of alcohol intake and AW may be cumulative and also interact with other independent pathophysiological processes: the development of neurodegenerative disorders, a vascular dysfunction, events such as seizures or strokes, nutritional depletion, etc., lowering the threshold of significant impairment and advancing the diagnosis.…”
Section: Alcohol Withdrawal and Severe Cognitive Impairmentsmentioning
confidence: 99%
“…TMAO is found in the cerebrospinal fluid, and could promote blood–brain barrier disruption, aggregation of Aβ protein and tau-tubulin assembly [ 14 ]. TMAO could also be involved in the perturbation of beta-amyloid and tau homeostasis and thus may play a role in the development of cognitive deficits in AUD patients [ 15 , 16 , 17 ]. Lastly, another recent experimental work showed that TMAO can contribute to brain aging [ 18 ].…”
Section: Introductionmentioning
confidence: 99%